(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
This was a cross-sectional study carried out among 120 students of National Ideal School in Dhaka city during September2012 to November2012. The objective of the study was to assess the level of knowledge about the effect of drug abuse. Students were selected by purposive sampling technique. A pretested semi structured questionnaire was used and data were collected by self-administered method. Analysed by computer program SPSS. On analyses, the students were found to have very poor knowledge regarding the causes of drug abuse, 50% stated about unemployment, 48% stated about drug abuse friend, and 39% due to illiteracy. About the type of various drugs- 74% mentioned the name of Heroin, 73% Phensidyle, 48% cigarette and 31% stated the name of Ganja. Knowledge about various diseases- 80% mentioned death, 63% said hepatitis-B, 34% stated stroke. Regarding the social effect- 45% stated about increased fatehood, 34% about increased dacoity, 27% mentioned about increased crime. Knowledge about the familial effect, 67% mentioned about familial disturbance, 53% about waste of money. Knowledge regarding the health effect, 46% mentioned about red eyes, 36% mentioned about vertigo, 48.% mentioned about malnutrition, 39% about damage of other organ. Knowledge about the mental effect, 56% mentioned about become angry, 54% about abnormal behaviour. 69% of the respondents said about the consequences of drug abuse, is unusual death, 58% through out of family, 30% damage of other organ. From above data the overall knowledge scoring was, poor knowledge 84.2%, average knowledge 15.8% and no good knowledge were scored by the students. It may be concluded that the secondary school students have poor knowledge about the effect of drug abuse. Therefore heath education program in the school on drug abuse should be arranged from the secondary school level. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16603 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 12-18